Experimental investigation of spray propagation under crossflow conditions with Shadowgraph and Schlieren techniques. Issue 2 (December 2020) - Zueva, T S; Weiss, L; Wensing, M; Garyaev, A B
Abstract: This paper is devoted to the description and analysis of the experimental results which were carried out to investigate sprays of liquid hydrocarbons under crossflow conditions. The experimental conditions corresponded to the injection conditions of gasoline sprays in a cylinder of an internal combustion engine. Two types of liquid hydrocarbons, isooctane and ethanol, were used as injected fuels. The injection pressure varied between 100 and 170 bar, the air crossflow velocity ranged from 0 till 50 ms -1 and the fuel temperature from 25 till 98 °C. Two optical methods, Shadowgraph and Schlieren, were used to visualize the spray movement over time. The boundaries of liquid and vapour spray phases as well as basic principles of spray propagation and evaporation under crossflow conditions were obtained after processing and analysing these images.